Brazilian nursing and scientific production about obstetric violence (Research, Society and Development, 2022)
Introduction: The high incidence of harmful events to women's health, which occur during the birth process, encourages the need to discuss obstetric violence and identify the scientific production of Brazilian Nursing on the subject. Objectives: to quantify the scientific productions of Nursing that discuss obstetric violence in perinatal care - pregnancy, childbirth and puerperium. Methodology: Descriptive research, with a quantitative approach of the bibliometric review type, of articles published between 2016 and 2021, selected from the descriptors and inclusion/exclusion criteria. Results: 39 suitable studies were identified. The Nursing Journal emerges as relevant in the subject of Obstetric Violence, being the vehicle of 6 of the 39 studies found. Twelve authors were found to be the main contributors to the production focused on obstetric violence. Among the most frequent terms we have: obstetric violence, obstetric interventions, institutional violence, gender violence, violence against women and harmful practices. Conclusion: It is expected that the results presented by the current study will encourage Obstetric Nursing to turn its gaze to research, as a tool for conquering women's rights, promoting quality care.